The Influence of Unit I Pidum Information Technology Mastery on the Effectiveness of Disclosure of Cheating Crimes at the Ngawi Police - Wiraguna, Farras Adyaksa; Krisna, Gede Bayu (Police Studies Review, 2024)
The crime of aggravated theft is a problem in law enforcement in Indonesia, especially at the district police level. The Indonesian National Police is adapting to the development of 4.0 era technology, making it important for the National Police to master information technology in law enforcement. This final project aims to examine the relationship between mastery of information technology and the effectiveness of disclosing aggravated theft at the Ngawi District Police. This research uses a survey method with questionnaires distributed to members of the Criminal Investigation Unit I at the Ngawi District Police. The results of multiple linear regression analysis show that the intensity of information technology has a negative and significant effect, while ease of information exchange and access to cooperation have a positive and significant effect on the effectiveness of disclosing aggravated theft. Investments in technology and the availability of experts do not significantly affect it. The results of the coefficient of determination test show that these variables together affect the effectiveness of disclosing aggravated theft at the Ngawi District Police by 84.0%.